Abundance of aposematic patterns in hooded skunk, Mephitis macroura - Monroy-Gamboa, Alina Gabriela; Lavariega, Mario C.; Ramos-Méndez, Dagoberto (Therya Notes, 2021)
Some organisms warn their predators through color patterns. This is the case of the hooded skunk, Mephitis macroura. Under the assumption that the coloration of skunks is aposematic, we analyzed the coloration patterns of a population of hooded skunks. We hypothesized that the individuals showing a more contrasting coloration, should be more abundant in open vegetation types than those with a less contrasting pelage coloration. Using camera-traps, we grouped photographs of hooded skunks showing different combinations of color patterns and determined the relative abundance of individuals by color patterns by set and habitat type. We identified 25 individuals in the study area, most of them in induced grasslands, and identified four combinations of color patterns. We found an overlap of the period of activity and space, as well as a higher abundance of the most contrasting color pattern in the most open type of vegetation, accepting our hypothesis. We contribute to a better understanding of the ecologic relations between the habitat and the possible adaptations of some species to their environment like the skunks.